Applying the DER rating system for the visual assessment of defects on concrete dams - Muhenje, Mariura (Department of Civil Engineering, 2021)
NamWater is responsible for the management and maintenance of Namibia's main dams, amongst the many other infrastructure assets under their ownership. They have, as a result, devised asset management policies and practices with the aim of reaping the benefits of asset management. Additionally, they have aligned themselves with the current approaches to dam safety management in managing the dams. These current approaches do however not provide for a guided and standard approach when it comes to the visual assessment of surface defects on the dam elements. This may result in varying assessment outcomes from different individuals based on their differences in training and experience. The DER rating system used for the rating of defects on road structures, as input into the STRUMAN BMS used by SANRAL and other entities, provides for a standard approach to visually assessing the defects on these road structures. A study by Gombele (2017:79) has also demonstrated the possibility of using the DER rating system for the assessment of defects on cooling towers in a power generation environment. Additionally, the rating of defects can also play a role in dam risk determination, as demonstrated in the CIRIA 1 Project RP568 risk assessment methodology (Morris, Hewlett and Elliott, 2000:15). In quest for a standard and guided approach for visually assessing surface defects on dam elements, this study applied the DER rating on selected elements of three NamWater dams. The approach was by initially identifying dam elements that are deemed equivalent to the bridge items in the TMH19: Part A. There are variations in the design and functions of the dam elements versus those of bridge elements and thus the relevance of the defects may also vary for the two structure types. Thus, the focus of this study was on using the DER rating system to only assess the surface defects on the dam elements. This may be useful for the initial phase of a condition assessment for dams whereby it can provide a quantifiable indication of durability issues. While the study was able to demonstrate the possibility of using the DER rating system to assess defects such as cracks, spalling and erosion on the surfaces of dam elements, gaps where identified in its applicability. Only 33% of the bridge items in the TMH19: Part A were deemed relevant for the visual assessment of the dam items, coupled with the significant amount of U (unable to inspect) ratings given during the assessment. Furthermore, of the identified defects, a significant amount was given a low Relevancy rating (R) meaning that they are of a low relevance to the structural integrity of the dam structure. This may be due to the fact that the guiding tables used are originally for bridge items and thus not entirely suitable for dams. For the DER rating system to be applied extensively to dam items, defects that are specific to dam elements will therefore need to be incorporated into the guiding tables. Additionally, the weighting of the ratings for certain defects would need to be revised to specifically align with the consequence of the defect on the dam item. This process may require the compilation of a database of historical defects, guided by expert engineering judgement, to provide for guiding tables that are specific to dams. Assessment of more dams that vary in age, type, and performance may also be required to get a more diversified outcome of the applicability of the DER rating system on dams.